Spirit-controlled temperament - LaHaye, Tim F., 1926-2016 (Tyndale House, 1966)
Everyone is a curious mixture of weaknesses and strengths, and there's a reason. Everyone has inherited a distinct temperament -- predominantly sanguine, choleric, melancholy, or phlegmatic, with a combination of traits from two or more groups. Given a person's natural temperament, the Holy Spirit can manifest supernatural characteristics in his life. God's Spirit can release an individual from a life of anger, fear, depression, indecisiveness, instability, and restlessness, and can give a new freedom of peace, purpose, self-control, and dignity.